Tetrahedral and Octahedral arrangements of resistors: An experimental activity using incandescent-halogen lamps - Leonardo Motta; Fernanda Sant’Anna; Rodrigo Rossini; Antonio Carlos Fontes dos Santos (Education and Development Research, 2025)
This article is the third in a trilogy, in which experimental activities involving classic symmetrical resistive circuits are proposed, where we draw attention to the fact that the use of halogen-incandescent lamps as resistors promotes an excellent visualization of symmetries or non-existences, through the comparison of the brightness of the lights, making the experimental activity a more playful and attractive practice for the student. This work aims to contribute to the small number of pedagogical experimental works involving symmetrical resistive electrical circuits, a proposal that approaches the subject in a playful and light way. Our methods use low-cost and easily accessible material. In the present paper, one focuses on the tetrahedral and octahedral cases. Both the theoretical development and the experimental analysis are presented and compared. The main implications are the importance of using arguments of symmetry as a pedagogical tool in solving problems (in the specific case, simplification-analysis of resistive electrical circuits) was evidenced in the analysis of the arrangements.